Neurobiological correlates of distinct PTSD symptom profiles during threat anticipation in combat veterans - Grupe, Daniel W. (Psychol Med, 2016)
BACKGROUND: Previous research in posttraumatic stress disorder (PTSD) has identified disrupted ventromedial prefrontal cortex (vmPFC) function in those with versus without PTSD. It is unclear whether this brain region is uniformly affected in all individuals with PTSD, or whether vmPFC dysfunction is related to individual differences in discrete features of this heterogeneous disorder. METHODS: In a sample of 51 male veterans of Operation Enduring Freedom/Operation Iraqi Freedom, we collected functional magnetic resonance imaging data during a novel threat anticipation task with crossed factors of threat condition and temporal unpredictability. Voxelwise regression analyses related anticipatory brain activation to individual differences in overall PTSD symptom severity, as well as individual differences in discrete symptom subscales (re-experiencing, emotional numbing/avoidance, and hyperarousal). RESULTS: The vmPFC showed greater anticipatory responses for safety relative to threat, driven primarily by deactivation during threat anticipation. During unpredictable threat anticipation, increased PTSD symptoms were associated with relatively greater activation for threat vs. safety. However, simultaneous regression on individual symptom subscales demonstrated that this effect was driven specifically by individual differences in hyperarousal symptoms. Furthermore, this analysis revealed an additional, anatomically distinct region of the vmPFC in which re-experiencing symptoms were associated with greater activation during threat anticipation. CONCLUSIONS: Increased anticipatory responses to unpredictable threat in distinct vmPFC subregions were uniquely associated with elevated hyperarousal and re-experiencing symptoms in combat veterans. These results underscore the disruptive impact of uncertainty for veterans, and suggest that investigating individual differences in discrete aspects of PTSD may advance our understanding of underlying neurobiological mechanisms.